Feasibility of laser-induced breakdown spectroscopy (LIBS) as an at-line validation tool for calcium determination in infant formula. (August 2017) - Cama-Moncunill, Xavier; Markiewicz-Keszycka, Maria; Dixit, Yash; Cama-Moncunill, Raquel; Casado-Gavalda, Maria P.; Cullen, Patrick J.; Sullivan, Carl
Abstract: In this study, a 150 mJ laser-induced breakdown spectroscopy (LIBS) system was assessed to determine calcium content in infant formula (IF) samples. LIBS is a promising emission spectroscopic technique for elemental analysis, which offers advantages over conventional methods such as real-time analyses, little to no sample preparation and ease of use. The aim of this work was to evaluate the feasibility of LIBS as an at-line tool for IF manufacturing. To this end, IF mixtures with varying content of calcium were prepared over a range (approx. 1.5–7 mg/g of calcium) selected to be in conformity with the guidelines provided by the Codex Alimentarius Commission. Atomic Absorption Spectroscopy (AAS) was used as the reference method for mineral content determination in IF. Partial least squares regression (PLSR) was applied to the LIBS spectral data to develop a calibration model for calcium content quantification. A validation approach was then carried out to investigate the robustness of the model, which showed a good fit with values of R 2 cv of 0.90 for cross-validation and a R 2 p 0.85 for external validation. Low values for root mean square errors of cross-validation (RMSECV) and prediction (RMSEP) of 0.62 mg/g and 0.68 mg/g were obtained. Furthermore, this study also illustrated the possibility of LIBS to provide mineral prediction maps as a useful tool for testing sample homogeneity. Highlights: LIBS as an at-line tool for infant formula manufacturing. Calcium content quantification via a novel LIBS system and chemometrics. Chemical maps for sample homogeneity assessment.